Risk Perceptions of Environmental Hazards and Human Reproduction: A Community-Based Survey. (5th October 2011) - Shepherd, Ashley; Jepson, Ruth; Watterson, Andrew; Evans, Josie M. M.
Abstract : Objectives . We have investigated the Australian public's perceived risks on human reproductive health from a number of identified environmental hazards. Methods . A sample of 1261 subjects was interviewed. This interview included specific questions related to perceived risks of certain environmental hazards to human reproductive health. Results . Women were almost twice as likely to rank all hazards as harmful or very harmful to human reproduction than men. Age also influenced perceived risk with those in the 35 and older age groups more likely to rank lead as a harmful hazard when compared with the 18–34 group. Pesticides were identified by 84.5% of the sample as the most harmful environmental hazard to human reproduction. Conclusions . Similar to other environmental hazards, different groups of people in the general population perceive hazards relating to reproductive health differently. This information is important for both policy makers and health professionals dealing with reproductive environmental health issues.